Methodological Considerations for Survey-Based Research During Emergencies and Public Health Crises: Improving the Quality of Evidence and Communication - Kennedy, Eric B; Jensen, Eric A; Jensen, Aaron M (Frontiers in Communication, 2022)
The novel coronavirus (COVID-19) outbreak has resulted in a massive amount of global research on the social and human dimensions of the disease. Between academic researchers, governments, and polling firms, thousands of survey projects have been launched globally, tracking aspects like public opinion, social impacts, and drivers of disease transmission and mitigation. This deluge of research has created numerous potential risks and problems, including methodological concerns, duplication of efforts, and inappropriate selection and application of social science research techniques. Such concerns are more acute when projects are launched under the auspices of quick response, time-pressured conditions–and are magnified when such research is often intended for rapid public and policy-maker consumption, given the massive public importance of the topic.